2020
DOI: 10.3390/pharmaceutics12070678
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Essential Oil Formulation: Chitosan Coated Nanoemulsions for Nose to Brain Delivery

Abstract: Brain infections as meningitis and encephalitis are attracting a great interest. Challenges in the treatment of these diseases are mainly represented by the blood brain barrier (BBB) that impairs the efficient delivery of even very potent drugs to reach the brain. The nose to the brain administration route, is a non-invasive alternative for a quick onset of action, and enables the transport of numerous medicinal agents straight to the brain thus workarounding the BBB through the highly vascularized olfactory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…[63] reported that thymol (46.3%) and p-cymene (22.1%) were identified as the main components of TEO. Rinaldi et al [64] showed the presence of thymol as the most abundant (44.4%) followed by O-cymene (18.2%) and linalool (7.5%) in the chemical composition of TEO. Based on these results, our essential oil shows a chemical composition proportionate to those mentioned by other authors who assume its memory-enhancing and antioxidant function.…”
Section: The Chemical Composition Of the Thymus Vulgaris Essential Oilmentioning
confidence: 99%
“…[63] reported that thymol (46.3%) and p-cymene (22.1%) were identified as the main components of TEO. Rinaldi et al [64] showed the presence of thymol as the most abundant (44.4%) followed by O-cymene (18.2%) and linalool (7.5%) in the chemical composition of TEO. Based on these results, our essential oil shows a chemical composition proportionate to those mentioned by other authors who assume its memory-enhancing and antioxidant function.…”
Section: The Chemical Composition Of the Thymus Vulgaris Essential Oilmentioning
confidence: 99%
“…The polymeric nanoemulsions were effective against multi-drug-resistant Gram-negative microorganisms causing meningitis. The nanoemulsions were completely biocompatible because of the natural origin of the components of nanoemulsions [ 46 ]. TAT-modified cationic peptide PA-28 is gaining interest because of its antibacterial properties.…”
Section: Nanomaterials: Applications In Meningitis and Bacterial Imentioning
confidence: 99%
“…Among the most important ones possible, drug degradation in nasal mucosa, limited capacity of the nasal cavity, and its high clearance are mentioned [ 36 ]. In order to improve the effectiveness of nose-to-brain drug delivery, different carriers are employed, including mucoadhesive formulations, polymeric [ 37 ], and lipid nanoparticles [ 38 ], micelles [ 39 ], nanostructured lipid carriers [ 40 ], nanoemulsions [ 41 ], and microemulsions [ 42 ].…”
Section: Introductionmentioning
confidence: 99%